An Overview of Alaskan's Prehistoric Cultures - Gillispie, Thomas E. (2018)
This report provides an overview which adopts a basic approach that describes the broadest outlines of Alaska’s prehistoric culture history as seen against the backdrop of these environmental changes and geographic divides. Results of the many more advanced analyses of prehistoric behavior are omitted for the sake of simplicity, as are the details of the many scholarly debates important in the archaeological literature.